PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (Ditinjau Dari Perspektif Yuridis Dan Sosiologis) - Wadi, Fajrul (Alhurriyah, 2012)
The issue in acquisition of land for public purposes until now is still create a problem in the midle of society even until create a conflict expecially between society and the govermment, in one side the goverment need the land for provision of public facilities but in the other side it arise denial from society to doing the submission and release land rights of them. Various laws have been formed for the acquisition of land for public use either in the form of a presidential decree to form of law, but the level of implementation is still causing controversy in the midle of society which often lead to social conflict. The reason is the regulation does not accommodate and provide legal protection to the public even tend to position people in a weak position, then the rules only focus on juridical aspects and prosedural aspects, but they ignore the sociological aspects so reasonable it will be repressive rule and does not reflect the sense of justice.